Traditions And Historical Development Of Folk Crafts In Uzbekistan (On The Example Of Khorezm) (Eurasian Journal of History, Geography and Economics, 2026)
Folk crafts represent one of the most ancient forms of human economic and cultural activity. They emerged as a result of the production activities of early societies and gradually separated from agriculture and animal husbandry in the process of social development. Over time, crafts developed in close connection with technological progress, natural resources, and the division of labor, forming numerous specialized branches such as pottery, carpentry, blacksmithing, metalworking, jewelry making, embroidery, leatherworking, weaving, and wood carving. This article analyzes the historical development of crafts in Uzbekistan, particularly in the Khorezm oasis, from ancient times to the present day. Special attention is paid to the influence of historical processes, natural conditions, and cultural traditions on the formation of craft practices. The study also examines the role of the Silk Road in the spread of craft products, the impact of political changes and conquests on craft development, and the revival of traditional crafts during the years of Uzbekistan’s independence. The research concludes that folk crafts constitute an important element of national cultural heritage and play a significant role in preserving traditional knowledge, supporting local economies, and promoting cultural tourism